Effect Of Pre-Treatment And Inoculant During Composting Of Palm Oil Empty Fruit Bunches - A.Y. Zahrim; I.K.T. Yee; E.S.C. Thian; S.Y. Heng; J. Janaun; K.P. Chong; S.K. Haywood; V. Tan; T. Asis; T.M.T.M.A. Al-Mizi (ASEAN Journal of Chemical Engineering, 2018)
In this work, untreated empty fruit bunch (EFB) or microwave-assisted NaOHpretreated EFB with palm oil mill effluent (POME) were composted under mesophilicconditions either in the presence or absence of Bacillus amyloliquefaciens D203 for sixtydays. During pretreatment conditions, the EFB was mixed with 1% (w/w) sodiumhydroxide and then exposed to microwave irradiation. The composting process wasevaluated based on the evolution of pH, electrical conductivity, moisture content, organicmatter loss, zeta potential and phytotoxicity. The strain Bacillus amyloliquefaciens D203 is not suitable for EFB-POME composting due to lower organic matter loss. The microwave-assisted NaOH pretreatment contributed to ~15% more organic matter loss than was found in the untreated sample while its germination index was >50%.